Le « paysage urbain » en question - Naouel Bchir Jaber (Projets de Paysage)
The article presents methodological choices of a research about the notion of urban landscape. The first part outlines the issues and problems about this notion (especially through the current debates between landscape professionals and theorists) and make clear reference fields of the study. The second part presents two directions of research selected. First, a genealogical approach focuses on the artistic and conceptual construction of the urban landscape. The second axis is part of a sociological approach by carrying out a qualitative inquiry, which section outlines the first conclusions.